The role of innovation adoption and circular economy readiness on the environmental sustainability: moderating impact of organizational support - Cardoza Sernaqué, Manuel Antonio (2022)
Environmental sustainability is currently the most critical demand on a global scale, and it may be reached through innovation and a circular economy. This component demands the aim of policymakers and researchers. Therefore, this study investigates the effect of innovation adoption and circular economy readiness on Peru's environmental sustainability. The research also examines the moderating effect of organizational support on innovation adoption, preparation for the circular economy, and environmental sustainability in Peru. Using questionnaires, the researchers collected and evaluated the data using smart PLS. The results demonstrated a positive relationship between innovation adoption, circular economy readiness, and environmental sustainability in Peru. The results also demonstrated that organizational support moderates’ innovation uptake, preparation for the circular economy, and environmental sustainability in Peru. The research aids policymakers in formulating environmental sustainability strategies based on innovation uptake and circular economy preparedness.